CURRENT STATE OF ADMINISTRATIVE AND LEGAL ENSURING OF INFORMATION SECURITY IN UKRAINE: THEORETICAL AND LEGAL ANALYSIS - Kaletnik, Vasyl (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: analysis of the current state of administrative and legal ensuring of information security in Ukraine, development of scientifically sound proposals and recommendations on this issue. Methods: in the study, the author used methods of theoretical analysis and content analysis, monographic method, method of systematization to identify and specify the author’s position within the studied issues. When preparing conclusions and recommendations based on the results of the study, the method of generalization was used. Results: the directions of increase of efficiency of administrative and legal ensuring of information security in Ukraine on the basis of realization of a complex of organizational and legal measures are defined. Emphasis is placed on the fact that the search for ways to effectively overcome the problems associated with the need to improve the administrative and legal support of information security in Ukraine should be based primarily on an in-depth analysis of all socio-political, economic and social processes in the country. Discussion: in the dynamic development of the information society, the security situation in the world is changing so fast that the legal and terminological support of the competent authorities responsible for state security, including in the information sphere, is significantly delayed, forcing them to act sometimes in a partial legal vacuum. In addition, the COVID-19 pandemic significantly accelerated processes that had previously developed rather slowly. Therefore, today there is a need to study the issue of administrative and legal ensuring of information security, which depends on the effectiveness of administrative and legal measures.